Vasodilation and Reduction of Systolic Blood Pressure after One Session of High-Intensity Interval Training in Patients With Heart Failure with Preserved Ejection Fraction - Lima,Juliana Beust de (2018)
Abstract Background: Heart failure with preserved ejection fraction (HFpEF) is a multifactorial syndrome characterized by a limited exercising capacity. High-intensity interval training (HIIT) is an emerging strategy for exercise rehabilitation in different settings. In patients with HFpEF, HIIT subacute effects on endothelial function and blood pressure are still unknown. Objective: To evaluate the subacute effect of one HIIT session on endothelial function and blood pressure in patients with HFpEF. Methods: Sixteen patients with HFpEF underwent a 36-minute session of HIIT on a treadmill, alternating four minutes of high-intensity intervals with three minutes of active recovery. Brachial artery diameter, flow-mediated dilation, and blood pressure were assessed immediately before and 30 minutes after the HIIT session. In all analyses, p <0.05 was considered statistically significant. Results: There was an increase in brachial artery diameter (pre-exercise: 3.96 ± 0.57 mm; post-exercise: 4.33 ± 0.69 mm; p < 0.01) and a decrease in systolic blood pressure (pre-exercise: 138 ± 21 mmHg; post-exercise: 125 ± 20 mmHg; p < 0.01). Flow-mediated dilation (pre-exercise: 5.91 ± 5.20%; post-exercise: 3.55 ± 6.59%; p = 0.162) and diastolic blood pressure (pre-exercise: 81 ± 11 mmHg; post-exercise: 77 ± 8 mmHg; p = 1.000) did not change significantly. There were no adverse events throughout the experiment. Conclusions: One single HIIT session promoted an increase in brachial artery diameter and reduction in systolic blood pressure, but it did not change flow-mediated dilation and diastolic blood pressure.